2011
DOI: 10.1242/jcs.069500
|View full text |Cite
|
Sign up to set email alerts
|

Cdc48/p97–Ufd1–Npl4 antagonizes Aurora B during chromosome segregation in HeLa cells

Abstract: SummaryDuring exit from mitosis in Xenopus laevis egg extracts, the AAA+ ATPase Cdc48/p97 (also known as VCP in vertebrates) and its adapter Ufd1-Npl4 remove the kinase Aurora B from chromatin to allow nucleus formation. Here, we show that in HeLa cells Ufd1-Npl4 already antagonizes Aurora B on chromosomes during earlier mitotic stages and that this is crucial for proper chromosome segregation. Depletion of Ufd1-Npl4 by small interfering RNA (siRNA) caused chromosome alignment and anaphase defects resulting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 58 publications
(97 reference statements)
7
44
0
Order By: Relevance
“…5, A and B). Studies have shown that VCP/p97 functions in regulating DNA metabolic processes by mediating proteasomal degradation or catalyzing the extraction of proteins or protein complexes from the chromatin (35,38). On the basis of this information and the data presented in our study, we propose that C1orf124 may function to stabilize Ub-PCNA and RAD18 on DNA damage sites by preventing their removal or extraction from the chromatin by VCP/p97 during TLS (Fig.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…5, A and B). Studies have shown that VCP/p97 functions in regulating DNA metabolic processes by mediating proteasomal degradation or catalyzing the extraction of proteins or protein complexes from the chromatin (35,38). On the basis of this information and the data presented in our study, we propose that C1orf124 may function to stabilize Ub-PCNA and RAD18 on DNA damage sites by preventing their removal or extraction from the chromatin by VCP/p97 during TLS (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…Recent studies imply that VCP acts by extracting protein complexes bound to chromatin rather than promoting protein degradation. For example, Aurora B has been shown to be extracted from mitotic chromosomes by VCP/p97 and its cofactors (35). Furthermore, VCP/p97 regulates DNA replication by mediating the removal of replication licensing factor Cdt1 that is bound to PCNA (36).…”
Section: C1orf124 Coordinates With Valosin-containing Protein (Vcp) Imentioning
confidence: 99%
“…The emerging consensus is that p97 binds a small number of cofactors forming "core" complexes, one of which is Ufd1-Npl4. Under certain cellular conditions additional adaptors either recruit or bind to p97 core complexes (17). The p97-Ufd1-Npl4 structures presented here begin to explain how additional p97 adaptors could bind to a p97-Ufd1-Npl4 core complex.…”
Section: Cryoem Analysis Reveals Different Conformations For P97-ufd1mentioning
confidence: 69%
“…There has been much speculation as to how p97 can interact with so many different adaptor proteins that contain common p97 interaction domains (17,38,44). The emerging consensus is that p97 binds a small number of cofactors forming "core" complexes, one of which is Ufd1-Npl4.…”
Section: Cryoem Analysis Reveals Different Conformations For P97-ufd1mentioning
confidence: 99%
See 1 more Smart Citation